2021
DOI: 10.3390/agronomy11040754
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle Selection and Adjuvant Impact on the Efficacy of Glyphosate and PPO-Inhibiting Herbicide Tank-Mixtures

Abstract: PPO-inhibiting herbicides in combination with glyphosate for postemergence applications is a common approach to manage glyphosate- and ALS-inhibitor-resistant weeds. PPO-inhibitors can reduce glyphosate translocation when applied in tank-mixtures, but adjuvants may be used to overcome this effect. Additionally, optimal droplet size may be affected by tank-mixtures of different herbicides and it can be crucial to herbicide efficacy. Field and greenhouse studies were conducted to investigate the impact of nozzle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…According to Rizwan et al (2018) , the application of herbicide increases the number of spike-bearing tillers (m –2 ) significantly. Our findings are further supported by Moraes et al (2021) who stated that herbicides applied with adjuvants either at full or reduced doses significantly decreased the weeds infestation than herbicides used alone and resultantly improved the spike-bearing tillers with concomitant reduction of non-spike-bearing tillers by supplying more space, light, and nutrients to crop plants. Further studies suggested that optimum weed control was based on the selection of herbicide and adjuvants along with weed-specific situations ( Javaid et al, 2012 ; Moraes et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…According to Rizwan et al (2018) , the application of herbicide increases the number of spike-bearing tillers (m –2 ) significantly. Our findings are further supported by Moraes et al (2021) who stated that herbicides applied with adjuvants either at full or reduced doses significantly decreased the weeds infestation than herbicides used alone and resultantly improved the spike-bearing tillers with concomitant reduction of non-spike-bearing tillers by supplying more space, light, and nutrients to crop plants. Further studies suggested that optimum weed control was based on the selection of herbicide and adjuvants along with weed-specific situations ( Javaid et al, 2012 ; Moraes et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are further supported by Moraes et al (2021) who stated that herbicides applied with adjuvants either at full or reduced doses significantly decreased the weeds infestation than herbicides used alone and resultantly improved the spike-bearing tillers with concomitant reduction of non-spike-bearing tillers by supplying more space, light, and nutrients to crop plants. Further studies suggested that optimum weed control was based on the selection of herbicide and adjuvants along with weed-specific situations ( Javaid et al, 2012 ; Moraes et al, 2021 ). Similarly, Khalil et al (2010) also revealed that greater numbers of spike-bearing tillers were obtained with the application of carfentrazone-ethyl + isoproturon as compared with weedy check treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Example of the coverage obtained (blue spots) in one of the experimental plots with the application of ultra-coarse droplets at a volume of 58 L ha -1 . Moraes et al (2021) studied the control of weeds with glyphosate, fomesafen, and lactofen using different droplet spectra at a spray volume of 187 L ha -1 . They concluded that ultra-coarse droplets had similar control results to medium droplets.…”
Section: Control Effectivenessmentioning
confidence: 99%
“…The importance of chemical inputs in shaping weed agricultural adaptation is clear in that the most significant agriculturally associated SNP (raw p-value = 8.551x10 -11 , [FDR corrected] q-value = 0.00062) falls just 80 kb outside the gene protoporphyrinogen oxidase (PPO)-the target of PPO-inhibiting herbicides (Fig 2B). PPO herbicides were widely used in the 1990s, but have seen a recent resurgence to control and slow the spread of glyphosate resistant weeds (25,26). Other genes with the strongest agricultural associations include ACO1, which has been shown to confer oxidative stress tolerance (27); HB13, involved in pollen viability (28) as well as drought and salt tolerance (29); PME3, involved in growth via germination timing (30); CAM1, a regulator of senescence in response to stress (31,32); and both CRY2 and CPD, two key regulators of photomorphogenesis and flowering via brassinosteroid signaling (33)(34)(35)(36) (Table S2).…”
Section: The Genome-wide Signatures Of Agricultural Adaptationmentioning
confidence: 99%